Perspectives on the Holocaust : essays in honor of Raul Hilberg - Pacy, James S.; Hilberg, Raul 1926-2007 (Westview Press, 1995)
This volume brings together original historical, literary, and philosophical analyses of the Holocaust by some of the world's leading scholars, including Yehuda Bauer, Christopher R. Browning, George Steiner, Alvin H. Rosenfeld, Richard L